Publishing and flourishing: writing for desire in higher education. Issue 3 (16th April 2021) - Heron, Marion; Gravett, Karen; Yakovchuk, Nadya
ABSTRACT: In the current performative climate of higher education, where academic outputs are highly valorised, professional academic writing has become 'high stakes' and is often framed as fraught with tension and anxiety. In this article, we contest the phrase 'publish or perish' and argue that is not necessarily helpful or, indeed, always true. Through interviews involving critical incidents with a team of academics, the authors found that tensions in experiences of scholarly writing do indeed exist. However, participants also reported on the affordances of the process of professional academic writing in terms of developing ideas, collaborations, and creating spaces for creativity and desire. We emphasise the juxtaposition of the value of creation with the value of the finished product and argue that writing for publication needs to be highlighted as a process permeated with learning opportunities for both early career researchers and more experienced academics.